The Importance of the Prenyl Group in the Activities of Osthole in Enhancing Bone Formation and Inhibiting Bone Resorption In Vitro - Yuan-Kun Zhai; Ya-Lei Pan; Yin-Bo Niu; Chen-Rui Li; Xiang-Long Wu; Wu-Tu Fan; Ting-Li Lu; Qi-Bing Mei; Cory J. Xian (International Journal of Endocrinology)
Osteoporosis treatment always aimed at keeping the balance of bone formation and bone resorption. Recently, prenyl group in natural products has been proposed as an active group to enhance the osteogenesis process. Osthole has both the prenyl group and bone-protective activities, but the relationship is still unknown. In this study we found that osthole exerted a potent ability to promote proliferation and osteogenic function of rat bone marrow stromal cells and osteoblasts, including improved cell viability, alkaline phosphatase activity, enhanced secretion of collagen-I, bone morphogenetic protein-2, osteocalcin and osteopontin, stimulated mRNA expression of insulin-like growth factor-1, runt-related transcription factor-2, osterix, OPG (osteoprotegerin), RANKL (receptor activator for nuclear factor-κB ligand), and the ratio of OPG/RANKL, as well as increasing the formation of mineralized nodules. However, 7-methoxycoumarin had no obvious effects. Osthole also inhibited osteoclastic bone resorption to a greater extent than 7-methoxycoumarin, as shown by a lower tartrate-resistant acid phosphatase activity and lower number and smaller area of resorption pits. Our findings demonstrate that osthole could be a potential agent to stimulate bone formation and inhibit bone resorption, and the prenyl group plays an important role in these bone-protective effects.